Category reporting in charitable giving : an experimental analysis - Li, Jingping (2018)
We examine the effect of category reporting on charitable giving, aiming to disentangle the publicity effect from the category effect. We compare subjects' donation decisions under three reporting plans: category reporting, where an honored category is prespecified and qualifying subjects were publicly acknowledged; category no reporting, where the same category was utilized but the qualifying donors were not publicly acknowledged; and no reporting, where neither category setting nor public reporting was utilized. We found that category reporting significantly increased average donations relative to no reporting, and that this superiority was due to the dual presence of the category setting and the public reporting. The category setting anchors donations toward the category threshold and increased the average donations when the threshold was modestly set. The public reporting, on the other hand, only worked at the highest category level. It further increased the donations by providing extra social‐image benefits. (JEL C90, C91, D64, H00)